The impact of halogen ions on the guest dependent spin crossover behaviour and porosity of Co(ii) one-dimensional coordination polymers [CoX2(4′-(4-pyridyl)-2, 2′:6′, 2′′-terpyridine)] (X = Cl and Br)1. Issue 30 (14th August 2015) - Ohtani, Ryo; Shimayama, Kodai; Mishima, Akio; Ohba, Masaaki; Ishikawa, Ryuta; Kawata, Satoshi; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
<x xml:space="preserve">Abstract</x> Halogen ions in the Co(ii) SCO–CPs [CoX2(pyterpy)] (X = Cl and Br) impacted on their SCO behaviour and porosity.